Synthesis and Biological Evaluation of m-PEG Attached Acridinedione Derivatives as Antimicrobial, Antioxidant and Anticancer Agents - Dey, Tathagata; Viswambaran Asharani, Indira (Asian Journal of Chemistry, 2021)
Among heterocycles, a wide variety of nitrogen heterocycles have been exploited to develop pharmaceutically important molecules. Particularly, acridines are clinically used potential drug candidates showing various pharmacological activities. Some of the novel m-PEG attached acridinediones 4(a-j) were synthesized with the readily available starting materials such as dimedone, glycine and aldehydes. Structures of the synthesized compounds were characterized by spectral techniques. The synthesized compounds (4a-j) were evaluated for in vitro antimicrobial, antioxidant and anticancer activities. Compounds 4d, 4e and 4g were found to produce potent antimicrobial activities against Gram-positive and Gram-negative organisms while 4c active against only Gram-positive organisms when compared with the standard, ciprofloxacin. On the other side, 4d and 4i produced potent antioxidant activity and 4a, 4d and 4g exhibited comparable anticancer properties.